Self-management of oral anticoagulation reduces major outcomes in the elderly - Siebenhofer, Andrea; Rakovac, Ivo; Kleespies, Caroline; Piso, Brigitte; Didjurgeit, Ulrike; for the SPOG 60+ Study Group (Thrombosis and Haemostasis, 2008)
Although many patients with long-term oral anticoagulation (OAC) can manage their medication safely and reliably themselves, no study on elderly patients has as yet assessed the safety and efficacy of OAC self-management with major thromboembolic and haemorrhagic complications as primary outcomes. In this multi-centre trial, patients aged 60 years or more were randomised into a self-management (SMG) (N=99) or routine care group (RCG) (N=96).The primary outcome was the combined endpoint of all thromboembolic events requiring hospitalisation and all major bleeding complications. Mean follow-up was 2.9 ± 1.2 and 3.0 ± 1.1 years in the SMG and RCG, respectively. In intention-to-treat analysis, 12 patients in the SMG versus 22 patients in the RCG reached a primary endpoint (hazard ratio [HR]: 0.50; 95% confidence interval [CI]: 0.25 to 1.00; p=0.049).
Keywords: Oral anticoagulation; self-management; elderly patients; randomized controlled trial